Structural controls of AuNR@mSiO2: tuning of the SPR, and manipulation of the silica shell thickness and structure. Issue 13 (16th March 2016) - Wu, Zihua; Zeng, Qiang; Wang, Haishui
Abstract : End-selective etching the AuNRs of AuNR@mSiO2 can be managed to produce cavity-possessing, rattle-type, hollow, and shape-adaptive silica-coated nanocomposites. Abstract : The pursuit of desirable longitudinal surface plasmon resonance (LSPR) of gold nanorods (AuNRs) and a suitable silica coating structure are two important aspects concerning mesoporous silica-coated gold nanorods (AuNR@mSiO2 ). This paper reports a simple approach to not only tailor the LSPR of AuNRs but also simultaneously control the structure and thickness of the silica shell after the silica coating process. Under acidic conditions, the use of O2 for end-selective etching of internal AuNRs shows good control over the aspect ratio of the AuNRs, thus enabling controllable tuning of the LSPR of AuNR@mSiO2 . Compared to other strong oxidants such as aqua regia, O2 provides a milder and more gentle etching atmosphere, which gives the etched AuNRs good uniformity and regularity. Results showed that the thermal treatment of AuNR@mSiO2 solution before the initiation of the etching reaction had important impacts on the silica shell structure. Thermal treatment in ethanol solution gave rise to an empty and open mesoporous shell, and the use of ethanol–water as the solvent caused thinning of the shell thickness, while the internal AuNRs were basically unaffected in both cases. Both the opening and reduced thickness of the mesoporous silica shell facilitate the etching of the AuNRs. In addition, the rigid-type of mesoporous silica framework exposed in ethanol solution led to generation of cavity-possessing, rattle-type and hollow AuNR@mSiO2 as etching proceeded; however, in ethanol–water solution, the silica shell gained a certain extent of fluidity, resulting in movement of silica to fill the cavities created by end-etching of the internal AuNR.